2010
DOI: 10.1007/s00436-010-2042-4
|View full text |Cite
|
Sign up to set email alerts
|

Repellence of essential oils of aromatic plants growing in Argentina against Aedes aegypti (Diptera: Culicidae)

Abstract: Mosquitoes are vectors of pathogens to humans and domestic animals and may also have economical impacts. One approach to prevent mosquito-borne diseases is bite deterrence through the application of repellents. Currently, there is an interest to search for alternative bioactive products to the synthetic active ingredients most widely used in insect repellents. Repellence against Aedes aegypti of essential oils extracted from Acantholippia salsoloides, Aloysia catamarcensis, Aloysia polystachya, Lippia integrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…suaveolens EO repellency was evaluated using the human bait technique to simulate the condition of human skin on which repellents will be applied, as reported by Schreck and Mc Govern (1989), Gleiser et al (2011) and Kamsuk et al (2006). Tests were conducted during the summer of 2011.…”
Section: Repellent Activitymentioning
confidence: 99%
“…suaveolens EO repellency was evaluated using the human bait technique to simulate the condition of human skin on which repellents will be applied, as reported by Schreck and Mc Govern (1989), Gleiser et al (2011) and Kamsuk et al (2006). Tests were conducted during the summer of 2011.…”
Section: Repellent Activitymentioning
confidence: 99%
“…Many compounds isolated and identified from plant EOs show toxic activity against mosquito larvae (Mathew et al 2009;Conti et al 2010) or can be used as ovicidals, oviposition deterrents, growth-and reproduction-inhibitors (Rajkumar and Jebanesan 2005;Pushpanathan et al 2006) or adult repellents (Gleiser et al 2011). The number of EOs showing repellent properties against mosquitoes continues to grow (Amer and Mehlhorn 2006a;Gillij et al 2008;Gleiser et al 2011;Conti et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, the repellent effect of these plants has been also tested against other insects; for instance, Gillij et al [11] found A. citriodora as one of the most promising EO of the fourteen plants test against Aedes aegypti. Moreover, Gleiser et al [21] showed a dose-dependent activity of the EO of A. polystachya against the same mosquito. Considering that the EO of A. citriodora contains also other compounds such as limonene (7.4%) with potential repellent effects, synergistic phenomena should not be discarded [22].…”
Section: Resultsmentioning
confidence: 99%